Design Contextual Teaching and Learning Approach On Geometry Learning Module - Dyah Tri Wahyuningtyas; Nury Yuniasih; Edy Bambang Irawan; Susiswo Susiswo (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Mathematical learning with contextual approach provides an opportunity for students to actively construct mathematical knowledge. In solving a problem which is start from the problems that can be imagined by students and giving them a freedom to find their own strategies to solve it. By posing a contextual problem, students in a stage can master the mathematic concept. The purpose of this research is to develop the design of Contextual Teaching and Learning approach on geometry learning module. This type of research is development research. The phases development of the model and learning tools are carried out in three steps, which are: (1) preliminary research, (2) prototyping phase. The result of design this prototype phase are: (1) design of the geometry learning module, (2) design tools of learning and (3) design of research instrument. The module component consists of: (1) module description, which consists of core competencies and basic competencies to be achieved; (2) the instruction for using the module, that consist of introduction, initial ability checks, activity sheets, conclusion, worksheet, assessment column, and answer key.